Physiological response of grapevine Vitis vinifera L. to grapevine leafroll associated viruses (GLRaV-1 and GLRaV-1 + GLRaV-3) - Melita Štrukelj; Jaka RAZINGER; Barbara GRUBAR; Uroš ŽIBRAT; Irena MAVRIČ PLEŠKO; Dominik Vodnik; Gregor UREK (Acta Agriculturae Slovenica)
Grapevine leafroll disease is one of the most severe viral diseases of grapevine caused by Grapevine leafroll-associated viruses (GLRaVs). Physiological processes were monitored on grapevines with single (GLRaV-1) and mixed (GLRaV-1 and GLRaV -3) viral infection under greenhouse conditions from June to September, in vegetation period 2014. In the mid of the season (July) negative effects of the virus infections on physiological processes were more severe in mixed than in single infection. The net-photosynthesis (Pn) of the leaves infected with GLRaV-1 and GLRaV-3 reached only a half of the Pn in GLRaV-1 infected grapevines. Similar reduction was found for stomatal conductance, transpiration and parameters related to photochemical efficiency (electron transport rate).